Unveiling the distribution and research patterns of Aspergillus spp. in Saudi Arabia: a systematic and bibliometric analysis - Alzahrani, Kholoud K. (Frontiers in Microbiology, 2025)
Aspergillus species play an important role in agriculture and human health, however their detection, distribution and research in Saudi Arabia have not yet been fully described. For this reason, the objective of this study was to review the progress, places where Aspergillus research is being carried out and its long-range strategies in Saudi Arabia over the last 54 years. Applying advanced bibliometric processes, we analyzed a 520 scientific articles recorded a 108 different Aspergillus species from 275 diverse environments. Research productivity demonstrated distinct evolutionary phases, progressing from limited output (1970–1980) through steady development (1990–2000) to remarkable acceleration during 2010–2018 (peaking at 41 publications in 2013), followed by stabilization at 11–22 publications annually. Institutionally, 33 Saudi universities contributed, with King Saud University leading (172 publications, 39%). International collaboration networks showed strong Egypt-Saudi partnerships complemented by linking with India, Australia, and the USA. The research detected main five species received significant research focus: A. niger (421 studies), A. flavus (297), A. fumigatus (204), A. terreus (174), and A. ochraceus (105), reflecting strategic prioritization of agricultural, industrial, and clinical significance. Samples of isolates were taken from a variety of locations, as soil (114 studies and encompassing 8 major subcategories), plants (184 sources) and food (32 sources) are the most common types. By analyzing strategic thematic mapping, it was found that the area successfully moved away from mainly medical issues toward a mix that includes agricultural, environmental and biotechnological matters. Details of multiple Aspergillus species in various Saudi Arabian habitats are important additions to global science and help meet local needs in farming, healthcare and industry. The results prove that concentrating efforts and developing institutions can enhance research and solve local problems.